The Significance of the Folk Symbols and Their Influence on The National Identity (Chosen samples from the Contemporary Iraqi Pottery): زينب كاظم صالح (Al-Academy, 2015)
The contemporary art culture is considered a resultant of preceding human civilizations from the early days. At the same time, it got closer to the local privacy, because the contemporary Iraqi potter worked hard to create new art, refusing to base his art on the early works, creating art pieces that contains properties to inherited art and their form significance, in order to create a new identity of his own, bringing an empowerment to his deepened civilization, with the goal to create national identity ideas from one hand, and entity and locality from another. Europeans also followed the direction of our civilization, such as (Picasso, Henry Moore, Barbra Hurth, Brankouzi, Hans Arp,..etc). From this point of view comes the importance of this research in obtaining the significance the folk symbols and their influence on the national identity, such as the works of (Saad Shakir, Shiniar Abdullah, Mohammed Al-Arabi, Torki Hussein, Suham Al-Saodi, Sajda Al-Mishaikhy, Abla Al-Azawi, Nuha Al-Radhi, Mahir Al-Sammeraie, and others). The research will study:A- The significance, as an idea and a meaning in the visual fieldB- The folk symbols, their reference and establishment, and their influence on the arts.This reseach is only focusing on the time frame (1990-2010).